Foreign investors' interests and corporate tax avoidance: evidence from an emerging economy - Salihu, Ibrahim Aramide; Sheikh Obid, Siti Normala; Annuar, Hairul Azlan (2014)
The inflows of foreign investments into the developing countries have called for concerns. The opportunity for profit shifting across their various operating outlets has made multinational companies tax avoidant in the host countries. This study, thus, examines the tax impact of foreign investors’ interests within the host developing economy. Using four similar measures of tax avoidance and three related measures of foreign investors’ interests, the sample data came from FTSE Bursa Malaysia Top 100 firms for the financial periods of 2009, 2010 and 2011. The analysis of the dynamic penal data using the system GMM estimator shows significant positive relationships between foreign investors’ interests and the measures of corporate tax avoidance among Malaysian large companies. Apart from being a useful guide for the selection of companies for tax audit, this result is also relevant for the proper evaluation of policies regarding foreign direct investment (FDI) in developing economies.